2012
DOI: 10.4062/biomolther.2012.20.6.532
|View full text |Cite
|
Sign up to set email alerts
|

Avicularin Inhibits Lipopolysaccharide-Induced Inflammatory Response by Suppressing ERK Phosphorylation in RAW 264.7 Macrophages

Abstract: suppresAvicularin, quercetin-3-α-L-arabinofuranoside, has been reported to possess diverse pharmacological properties such as anti-inflammatory and anti-infectious effects. However, the underlying mechanism by which avicularin exerts its anti-inflammatory activity has not been clearly demonstrated. This study aimed to elucidate the anti-inflammatory mechanism of avicularin in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells. Avicularin significantly inhibited LPS-induced excessive production of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
4
49
0
Order By: Relevance
“…In addition, we recently demonstrated that N - ( p -coumaryol)-tryptamine significantly inhibited LPS-induced inflammatory responses through the suppression of JNK activation in RAW264.7 cells (Vo et al ., 2014). Furthermore, we also observed that that ERK signaling pathway was activated with LPS treatment and its activation and abnormal inflammatory responses were significantly attenuated with avicularin in LPS-challenged RAW264.7 cells (Vo et al ., 2012). No noticeable changes were observed in phosphorylation p38 with QG, indicating that QG exerts its anti-inflammatory action through the selective inhibition of JNK and ERK signaling pathways in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In addition, we recently demonstrated that N - ( p -coumaryol)-tryptamine significantly inhibited LPS-induced inflammatory responses through the suppression of JNK activation in RAW264.7 cells (Vo et al ., 2014). Furthermore, we also observed that that ERK signaling pathway was activated with LPS treatment and its activation and abnormal inflammatory responses were significantly attenuated with avicularin in LPS-challenged RAW264.7 cells (Vo et al ., 2012). No noticeable changes were observed in phosphorylation p38 with QG, indicating that QG exerts its anti-inflammatory action through the selective inhibition of JNK and ERK signaling pathways in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 84%
“…Given the previous studies that quercetin and its glycoside derivatives have pharmacological properties such as anticancer, anti-inflammatory, and anti-oxidant actions (Jagtap et al ., 2009; Pocernich et al ., 2011; Vo et al ., 2012; Yang et al ., 2014), the present study demonstrated that QG, a glucuronic acid glycoside of quercetin, possesses anti-inflammatory properties in LPS-induced RAW264.7 macrophage cells. In addition, the underlying mechanism by which QG exert the anti-inflammatory activity has not been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations